Multifunctional two dimensional Bi2Se3 nanodiscs for combined antibacterial and anti-inflammatory therapy for bacterial infections. Issue 33 (8th April 2019) - Ouyang, Jiang; Wen, Mei; Chen, Wansong; Tan, Yanni; Liu, Zhenjun; Xu, Qunfang; Zeng, Ke; Deng, Liu; Liu, You-Nian
Abstract : A multifunctional platform based on two-dimensional Bi2 Se3 nanodiscs for combined antibacterial and anti-inflammatory therapy is developed. Abstract : A multifunctional platform based on two-dimensional nanomaterials for combined antibacterial and anti-inflammatory therapy is developed. Bi2 Se3 nanodiscs selectively eradicate Gram-positive bacteria with a low risk of drug resistance. Moreover, Bi2 Se3 nanodiscs with antioxidant activity relieve intracellular oxidative stress of macrophages to suppress inflammation caused by bacterial infections.